Protein binding on acutely toxic and non-toxic polystyrene nanoparticles during filtration by Daphnia magna. Issue 7 (10th June 2022) - Kelpsiene, Egle; Brandts, Irene; Bernfur, Katja; Ekvall, Mikael T.; Lundqvist, Martin; Teles, Mariana; Cedervall, Tommy
Abstract : Toxic and non-toxic polystyrene particles bind different proteins during filtration by zooplankton. Abstract : Nanomaterials can adsorb biomolecules to their surface and form a protein corona. Here we investigated the protein profile bound to different sizes of aminated and carboxylated polystyrene (PS) nanoparticles after passing through the digestive tract of the freshwater zooplankter Daphnia magna . We found that acutely toxic aminated 53 nm PS nanoparticles bind a different set of proteins compared to other non-toxic PS nanoparticles. The aminated PS nanoparticles bind a higher number of proteins, which are smaller and more acidic, compared to the proteins which bind to the PS nanoparticles that are non-toxic in acute toxicity tests. The proteins bound to toxic nanoparticles can be divided into two groups. One group of proteins which function is related to the digestive system, whereas the other group of proteins can be related to the epithelium, intracellular structures and processes. Finally, we observed that not only proteins bind to the surfaces of the nanoparticles. Triglycerides effectively bind to 200 nm carboxylated PS nanoparticles but not to the other tested nanoparticles. These results provide information about the composition of the corona formed on surfaces of nanoparticles after a short-term incubation with D. magna and give insights to what underlies the acute toxicity caused by nanoparticles.